A study on awareness of organic food products in Trichy district - B., Rock; K., Puhalenthi; S., Vishnupriya; R., Pavithra; A. S., Supriya; K., Gayathri (International Journal Of Community Medicine And Public Health, 2017)
Background: The high growth of population and life expectancies during the recent years increased demand for food supplies in India. To meet this, the green revolution became the corner stone of agricultural achievement. Overexploitation of natural and non-renewable resources has impaired ecological balance and has put the health of the consumers in jeopardy. Therefore it is inevitable to resort to organic food products. The aim of the study was to assess the awareness of organic food products among the consumers in Trichy district, Tamil Nadu. Methods: A cross sectional questionnaire based study was conducted among rural, semi-urban, urban residents (100 each, total of 300) in august 2016. Results: Out of 300 respondents, 76%, 73%, 62% of the respondents have heard known about, and purchase organic food products respectively. The main source of organic foods was from specific shops and kitchen gardens and the most preferred factor while purchasing food items is the credibility. Though 62% of consumers purchase organic food, they mainly prefer vegetable and fruits and 38% of the respondents consume organic food regularly. The reason for not consuming organic foods in our residents is the non-availability. Conclusions: Awareness of organic food products among study population is about 76% with the greater awareness level among urban population. The main reasons for consuming organic food being credibility & availability. Increasing the awareness level of organic products, encouraging people to create their own organic garden can increase consumption of organic foods.